Heart failure with recovered ejection fraction (HFrecEF): A new entity with improved cardiac outcome. Issue 12 (4th November 2021) - Zeller, Judith; Hubauer, Ute; Schober, Andreas; Schober, Alexander; Keyser, Andreas; Fredersdorf, Sabine; Uecer, Ekrem; Maier, Lars S.; Jungbauer, Carsten
Abstract: Background: Aim of the study was a better characterization of heart failure (HF) with recovered ejection fraction (HFrecEF) and undulating EF (HFuEF) with regard to re‐hospitalization due to congestive HF (CHF), adequate electric therapies (AETs) and mortality compared to HF with reduced EF (HFrEF), mid‐range EF (HFmrEF) and preserved EF (pEF). Methods: Retrospective study of 342 participants with an implantable cardioverter defibrillator (ICD) for primary or secondary prevention. Type of HF was classified according to left ventricular EF with 4.7 ± 3.1 investigations for each patient. Results: Re‐hospitalization due to CHF was similar in HFrecEF (7 (9.5%)), HFmrEF (2(9.0%)) and pEF (8(12.9%); p = n.s.) and significantly higher in HFrEF (62(38.0%)) and HFuEF (6(28.6%); p < .001 compared to HFrecEF and HFrEF). AETs were significantly lower in HFrecEF (13(17.6%)) compared to HFrEF (57(35.0%)), HFmrEF (7(31.8%)), pEF (18(29.0%)) and HFuEF (6(28.6%); each p < .01 compared to HFrecEF). Mortality was similar in HFrecEF (6(8.1%)) compared to HFuEF (0(0%)), pEF (4(6.5%)) and HFmrEF (2(9.0%), p = n.s.) and significantly lower compared to HFrEF (52(31.9%), p < .001). HFrEF was the strongest predictor for mortality besides age and chronic renal insufficiency according to Cox Regression (each p < .05) opposite to arterial hypertension, diabetes, type of cardiomyopathy and secondary prevention ICD indication (each p = n.s.). Conclusions: HFrecEF indicates as a new entity of HF with similar prognosis as pEF and HFmrEF with regard to re‐hospitalization due to CHF and mortality and even better prognosis with regard to AETs. HFuEF showed similar rates of re‐hospitalization due to CHF and AETs compared to HFrEF, but lower rates of mortality.